Measuring Perceptual Reflections of Employees for Their Executives Intellectual Traits That Effecting Quality of Work Life of Employees and Organizational Change - Top, Seyfi; Öge, Ercan; Dilek, Serkan; Atan, Özlem (Springer Netherlands, 2013)
The aim of this study is to measure the relationship between the manager-leader’s intellectual features and the quality of work life (QWL) and organizational change (OC) by the perceptual reflections of employees’ perspective. Executives’ intellectual properties were found positively and significantly correlating with dependent variables of the study. We obtained statistically significant, positive (linear) and strong correlations between intellectual dimensions (vision and imagination, strategic perspective and critical analysis and judgement) and quality of work life in both intrinsic and extrinsic satisfaction dimensions. Also there were statistically significant, positive and strong correlations between intellectual dimensions and organizational change in both organizational innovation and organizational learning.
Keywords: 13. Climate action; 7. Clean energy